Abstracts of Scottish Vision Group 2022 Meeting - Jasna Martinovic; Nika Adamian; Mauro Manassi (Vision, 2022)
Since it was first launched in 2001, the Scottish Vision Group (SVG) has been a key meeting for vision scientists in Scotland, and has attracted vision scientists from the United Kingdom, Europe and beyond. This small conference is held annually at different places in Scotland. Its friendly atmosphere and stunning Scottish sceneries provide a great environment for relaxed scientific discussions. In particular, it is an excellent opportunity for scientists at an early stage of their career to give a talk about their work. The 2022 edition of SVG was held in St Leonard’s Hall at the University of Edinburgh. The meeting started with a panel discussion on camouflage led by Prof Nick Scott-Samuel (University of Bristol), Dr George Lovell (Abertay University) and Dr Rebecca Sharman (Abertay University). Research into camouflage has expanded remarkably over the last decade or so, with interdisciplinarity proving to be a key feature for progress. The discussion focussed on the different types of objectives and research techniques that are prominent in the field. The round table was sponsored by Meta Reality Labs. In the keynote lecture, sponsored by MDPI Vision, Prof Ute Leonards (University of Bristol) discussed the outcomes of her research programme investigating the crosstalk between visual cognition research and locomotion research. The outcomes of this Gibsonian approach do not just provide important insights into active vision but also outline the promising possibilities of sustainable urban design inspired by vision sciences. The rest of the conference was dedicated to talks on a variety of topics, including, but not limited to, attention, eye movements, visual search, motion perception, multisensory perception, colour and 3D vision. We present a selection of these abstracts. An associated Special Issue captures in fuller detail some of the research presented at SVG’s 2022 edition.